1994
DOI: 10.1155/s1064744994000232
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis C Virus Antibody in Patients With Sexually Transmitted Diseases Attending a Harrisburg, PA, STD Clinic

Abstract: Objective: The prevalence of hepatitis B and hepatitis C in a sexually transmitted disease (STD) clinic population was studied, along with the prevalence of various STD agents, in an attempt to identify possible STD markers for the hepatitis C virus and help delineate the role of hepatitis C as an STD. The hepatitis C antibody rates found in the STD clinic were also compared with those found among patients attending a local OB/GYN clinic and those enrolled in a blood donor program, all from the same geograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In other cases, the risk was larger when related to the presence of other factors, such as multiple sexual partnerships, the presence of sexually transmitted diseases and, primarily, concomitance with HIV infection 10,11 . Other studies reporting associations between HCV infection and STDs have produced varying results 12,13 . In the present study, univariate analysis indicated an association between HCV infection and sexual contact with HCV carriers, although this behavior was also less frequent, largely among subjects of the control group (2.1%).…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, the risk was larger when related to the presence of other factors, such as multiple sexual partnerships, the presence of sexually transmitted diseases and, primarily, concomitance with HIV infection 10,11 . Other studies reporting associations between HCV infection and STDs have produced varying results 12,13 . In the present study, univariate analysis indicated an association between HCV infection and sexual contact with HCV carriers, although this behavior was also less frequent, largely among subjects of the control group (2.1%).…”
Section: Discussionmentioning
confidence: 99%